Effect of annealing temperature on the structural and optical properties of nanocrystalline ZnO thin films prepared by sol-gel method - Ibrahim, N.B.; Al-Shomar, S.M.; Ahmad, S.H. (Universiti Kebangsaan Malaysia, 2013)
Undoped zinc oxide (ZnO) thin films were prepared by a sol-gel method. The effect of annealing temperature from 500 to 700°C on the structural and optical properties of the films was studied. The films nanostructure characterized by the X-ray diffraction method showed that the films were single phase ZnO with wurtzite structure. The surface morphology studied using the field emission scanning electron microscope showed that the thickness of the films increased with the increment of annealing temperature. The grain size of the films increased with the increment of the annealing temperature. The film surface roughness measured using the atomic force microscope showed that the surface roughness of the film decreased (from 2.3 to 1.02 nm ), when the annealing temperature increased from 500 to 600°C then it increased to 3.06 nm at 700°C. The optical properties were studied by the UV-Vis spectrophotometer. The results showed that the films had high transmittance (above 80%) in the visible range and the exciton absorption occurred at a wavelength of 379 nm. The energy gap decreased with the increment of annealing temperature.